Oropharyngeal Candida species in individuals living with HIV in Semarang: Distribution and antifungal susceptibility patterns - Masfiyah, Masfiyah; Rahayu, Rahayu; Mujayanto, Rochman (Journal of Advanced Multidisciplinary Research, 2025)
Candidiasis is an infection caused by Candida species, which is the most common fungal infection. The prevalence of this infection increases with the rise in immunocompromised cases, such as HIV/AIDS. This study aims to determine microbiological data on Candida species infection and colonization, including types and susceptibility testing to fluconazole and voriconazole. This research is descriptive in nature. The study population consisted of people living with HIV who were screened by taking saliva samples, which showed the growth of Candida species. Identification of Candida species was performed using Gram staining, germ tube tests, and color identification in Hicrome Candida agar medium. Susceptibility testing was conducted using the Kirby-Bauer method for fluconazole and voriconazole. The diameter of the inhibition zone of Candida was measured and compared with CLSI (Clinical and Laboratory Standards Institute) standards. A total of 91 Candida species isolates were found. Candida albicans was the most frequently isolated species (75%), followed by Candida tropicalis (11%), Candida krusei (10%), and Candida glabrata (4%). The sensitivity of Candida albicans to fluconazole and voriconazole was 98.5%, while Candida tropicalis showed 100% sensitivity. Candida albicans remains the most prevalent isolate and is still sensitive to fluconazole and voriconazole.